Modelling, Simulation and Experimental Analysis of a Metal-Polymer Hybrid Fibre Based Microstrip Resonator for High Frequency Characterisation. (2016) - Schimmack, Manuel; Taute, Wolfgang; Hoeft, Michael
Abstract: Conductive multifilament fibres are the fundamental core for wearable technology in the biomedical engineering fields, as conductors in sensors or in bio-sensing textiles for healthcare. This contribution presents a model, simulation and the experimental analysis of a metal-polymer hybrid fibre based microstrip resonator for high frequency characterisation. The high frequency electromagnetic field simulation (HFSS) by ANSYS® is used for the modelling and finite element based simulation. It follows the design and manufacturing of the metal-polymer hybrid fibre based microstrip resonator for analysis of the scattering parameter measurements and the quality factors to 10 GHz with a vector network analyser (VNA) by Rohde & Schwarz®. Simulations and analysis also compare solid matter wire with the metal-polymer hybrid fibre.